A Plant Stress-Responsive Bioreporter Coupled With Transcriptomic Analysis Allows Rapid Screening for Biocontrols of Necrotrophic Fungal Pathogens - Belt, Katharina; Foley, Rhonda C.; O’Sullivan, Cathryn A.; Roper, Margaret M.; Singh, Karam B.; Thatcher, Louise F. (Frontiers in Molecular Biosciences, 2021)
Streptomyces are soil-borne Actinobacteria known to produce a wide range of enzymes, phytohormones and metabolites including antifungal compounds, making these microbes fitting for use as biocontrol agents in agriculture. In this study, a plant reporter gene construct comprising the biotic-stress responsive GLUTATHIONE S-TRANSFERASE promoter GSTF7 linked to a luciferase output (GSTF7:luc) was used to screen a collection of Actinobacteria candidates for manipulation of plant biotic stress responses and their potential as biocontrol agents. We identified a Streptomyces isolate (KB001) as a strong candidate and demonstrated successful protection against two necrotrophic fungal pathogens, Sclerotinia sclerotiorum and Rhizoctonia solani, but not against a bacterial pathogen (Pseudomonas syringe). Treatment of Arabidopsis plants with either KB001 microbial culture or its secreted compounds induced a range of stress and defence response related genes like pathogenesis related (PR) and hormone signalling pathways. Global transcriptomic analysis showed both treatments shared highly induced expression of reactive oxygen species and auxin signalling pathways at 6 and 24 hours post-treatment, while some other responses were treatment specific. This study demonstrates that GSTF7 is a suitable marker for the rapid and preliminary screening of beneficial bacteria and selection of candidates with potential for application as biocontrols in agriculture, including the Streptomyces KB001 that was characterised here and could provide protection against necrotrophic fungal pathogens.